Efficacy and safety of vaginal suppositories containing combination of Natamycin and Lactulose in treatment of vulvovaginal candidiasis: international, randomized, controlled, superiority clinical trial (combination of Natamycin and Lactulose for treatment of vulvovaginal candidiasis) - Oksana N. Volkova; Elena V. Amel’chenko; Oksana V. Makeeva; Sergey A. Tolmachev; Ekaterina A. Lesovaya; Lefteris C. Zacharia; Alexander V. Dikovskiy (BMC Women's Health)
Abstract Background The study aimed to assess the efficacy and safety of Natamycin + Lactulose vaginal suppositories (100 mg natamycin and 300 mg lactulose) (AVVA RUS JSC, Russia) in adult females with vulvovaginal candidiasis. Methods and Results An international, randomized, controlled, assessor-blinded clinical trial enrolled 218 females randomly distributed into three groups: Natamycin + Lactulose (92 patients), Lactulose (36 patients), and Pimafucin® (90 patients). The study drug and comparator drugs had an identical dosing regimen (one suppository intravaginally once a day at bedtime for six days). The study involved four visits to the study site with examination at Visits 2 and 3. The fixed-dose combination of Natamycin + Lactulose was superior to both comparator drugs in terms of the primary efficacy endpoint defined as the percentage of patients achieving a clinical recovery: the absence of symptoms of vulvovaginal candidiasis. At Visit 2, clinical recovery was reported in 81.6% of females in the Natamycin + Lactulose group compared to 42.9% and 62.3% of patients in the Lactulose and Pimafucin groups, respectively. The difference in proportions was 38.8% and 18.4%. In the Natamycin + Lactulose group, microscopic recovery was observed in 75.9% of patients at Visit 2 and in 90.8% of patients at Visit 3. In the Lactulose group, 45.7% and 74.3% subjects responded positively at Visits 2 and 3. In Pimafucin group, microscopic recovery was reported in 71.3% and 88.5% of patients at Visits 2 and 3, respectively, while no differences were observed between the Natamycin + Lactulose and Pimafucin groups at both visits. At Visit 3, the number of vaginal lactobacilli was significantly higher in the Natamycin + Lactulose group. In females with the low baseline content of vaginal lactobacilli, the combination drug under investigation increased the vaginal lactobacilli content to the reference values in 15.4% and 20.9% of patients at Visit 2 and Visit 3, respectively. Conclusions The fixed-dose combination Natamycin + Lactulose 100 mg + 300 mg vaginal suppositories (AVVA RUS JSC, Russia) demonstrated superior efficacy compared to 1) Pimafucin 100 mg and 2) Lactulose 300 mg vaginal suppositories in adult females with vulvovaginal candidiasis. Trial registration NCT06411314, retrospectively registered on May, the 13th, 2024.